Pengaruh Price Discount, Store Atmosphere, Display Product, dan Kualitas Produk terhadap Pembelian Impulsif (Studi Kasus di Matahari Department Store Sidoarjo) - Barutu, Risca Noviana; Yani, Muhammad; Nugroho, Tovan Tri (Universitas Batanghari Jambi, 2024)
The purpose of this research is to analyze the influence of price discounts, store atmosphere, product display, and product quality on impulse purchases at Matahari Department Store Sidoarjo. The research was carried out using a quantitative approach. The method used was purposive sampling with a sample size of 100 consumers of Matahari Department Store Sidoarjo. The data analysis technique uses multiple linear regression analysis techniques. The results of this research found that the price discount and product display variables had a positive and significant effect on impulsive purchases, store atmosphere and product quality had a negative effect on impulse purchases at Matahari Department Store Sidoarjo.